Pelayanan Kesehatan bagi Lansia di Desa Bantulan Sleman melalui Kolaborasi Dokter Umum dan Dokter Spesialis - Arie Nugroho; Taufik Nur Yahya; Ahmad Mufattan; Viviane Annisa (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
Bantulan Village, located in Godean District, Sleman Regency, is an area with a relatively high elderly population. However, most of the elderly in this area have not received comprehensive health services, especially from specialist doctors capable of treating chronic complaints often experienced by the elderly, such as joint pain, mobility disorders, and heart or lung disease. Therefore, a Free Health Service activity was held. This series of activities was carried out by a social project team from the Department of Surgery, Faculty of Medicine, University of Indonesia (UII), several members of which are health workers, namely general practitioners, orthopedic specialists, and thoracic surgeons. The social project will take the form of free health checks by general practitioners, orthopedic specialists, and thoracic surgeons, distribution of free medicines by pharmacists, free health consultations, and provision of education and referrals for patients requiring further management. This activity shows the high enthusiasm of the residents in carrying out this activity.